Effects of different inertial measurement unit sensor-to-segment calibrations on clinical 3-dimensional humerothoracic joint angles estimation - Bonfiglio, A.; Farella, E.; Tacconi, D.; Bongers, R. M. (Journal of Applied Biomechanics, 2024)
Calibrating inertial measurement units (IMUs) involves converting orientation data from a local reference frame into a clinically meaningful reference system. Several solutions exist but little work has been done to compare different calibration methods with each other and an optical motion capture system. Thirteen healthy subjects with no signs of upper limb injury were recruited for this study and instrumented with IMU sensors and optical markers. Three IMU calibration methods were compared: N-pose calibration, functional calibration, and manual alignment. Subjects executed simple single-plane single-joint tasks for each upper limb joint as well as more complex multijoint tasks. We performed a 3-way analysis of variance on range of motion error, root mean squared error, and offset to assess differences between calibrations, tasks, and anatomical axes. Differences in the 3 IMU calibrations are minor and not statistically significant for most tasks and anatomical axes, with the exception of the offset interaction calibration × axes (P < .001, n2G = .056). Specifically, manual alignment gives the best offset estimation on the abduction/adduction and internal/external rotation axes. Therefore, we recommend the use of a static N-pose calibration procedure as the preferred IMU calibration method to model the humerothoracic joint, as this setup is the simplest as it only requires accurate positioning of the trunk sensor.